Predictors Of Intercultural Competence, Internationalization At Home, And Global Citizenship Among Domestic Students In Malaysian Research Universities - Khalid, Jamshed (2020)
Internationalization, particularly Internationalization at Home (IaH) is of increasing interest in many universities worldwide and considered as a strategic priority to respond to the challenges of globalization. IaH offers international and global perspectives through formal and informal learning to all students which transforms them as global citizens. Despite the fact that 64% of European universities involved in IaH, there is an inadequacy regarding the institutionalization of the concept in developing countries such as Malaysia. A scarcity of research is evident regarding IaH from the